The Correlation Between the OTA/AO Classification System and Compartment Syndrome in Both Bone Forearm Fractures. Issue 11 (November 2017) - Auld, Thomas S.; Hwang, John S.; Stekas, Nicholas; Gibson, Peter D.; Sirkin, Michael S.; Reilly, Mark C.; Adams, Mark R.
Abstract : Objective: To evaluate the efficacy of using the Orthopaedic Trauma Association (OTA/AO) classification for both bone forearm fractures in predicting compartment syndrome. Design: Retrospective cohort. Setting: Level 1 Academic Trauma Center. Patients/Participants: One hundred fifty-one patients 18 years of age and older, with both bone forearm fractures diagnosed from 2001 to 2016 were categorized based on the OTA/AO classification. Patients with both bone fractures caused by gunshot wounds were excluded. Main Outcome Measurements: The endpoint for our study was whether forearm fasciotomies were performed based on the presence of compartment syndrome. Results: Of a total of 151 both bone forearm fractures, 15% underwent fasciotomy. Six of 80 (7.5%) grouped 22-A3, 8 of 44 (18%) grouped 22-B3, and 9 of 27 (33%) grouped 22-C underwent fasciotomies for compartment syndrome ( P = 0.004). The relative risks of developing compartment syndrome for group 22-B3 versus 22-A3 was 2.42 ( P = 0.08), 22-C versus 22-B3 was 1.83 ( P = 0.15), and 22-C versus 22-A3 was 4.44 ( P = 0.002). Conclusions: There is a significant correlation between the OTA/AO classification and the need for fasciotomies, with group C fractures representing the highest risk. Clinicians can use this information to have a higher index of suspicion for compartment syndrome based on OTA/AO classification to help minimize the risk of a missed diagnosis. Level of Evidence: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.